Optimization of Multi-branch Truss-Z based on evolution strategy. (October 2016) - Zawidzki, Machi
Highlights: New bio-inspired nomenclature for multi-branched Truss-Z (MTZ) network is introduced. Encoding, cost function & genetic operations for MTZs are introduced and illustrated. Experiments show that the introduced operators allow to create any desirable MTZ. Realistic application: "Multi-branch bridge" linking 6 terminals is presented. The illustrative network links pedestrian and cycling communication paths. Abstract: This paper concerns multi-branch Truss-Z networks (MTZ). A possible scenario for creating a "multi-branch bridge" linking 6 terminals of pedestrian and cycling communication is presented. This process is formulated as a constrained minimization problem. New, biology-inspired nomenclature for MTZ and encoding for MTZ are introduced. Several operations for MTZs are introduced and illustrated. The functionality of these operations is illustrated with transformation from a random MTZ to a "proper" 6-branch MTZ network. A population-based heuristic experiment is presented to demonstrate that the introduced operators allow us to create any desirable MTZ. A cost function for the considered scenario is introduced. The genetic operations are interpreted and visualized. A number of feasible MTZ layouts produced by an evolution strategy-based algorithm are presented. One of these layouts is used for creation of the spatial 6-terminal MTZ, which is also visualized.